A case of superior mesenteric artery syndrome characterized by deep forward bending posture in a cross‐legged position on the floor. Issue 4 (22nd April 2023) - Isono, Hiroki; Nakanishi, Koki
Key Clinical Message: A 17‐year‐old healthy male presents with severe epicardial pain and frequent vomiting 1 h after lunch, preferring to sit cross‐legged on a stretcher with a deep forward bending posture along with difficulty lying down. SMA syndrome should be considered in the differential diagnosis of patients demonstrating such posture. Abstract : If a patient presents with abdominal pain and vomiting that is relieved in cross‐legged, forward‐bending position on the floor, SMA syndrome should be considered in the differential diagnosis.